Impact of the immunohistochemical panel on patients with breast cancer diagnosis cared for in a referral hospital in the state of Amazonas - Pereira, Hilka Flávia Barra Espírito Santo Alves; Pereira, Roberto Alves; Silva, Thais Cristina Fonseca da; Pereira, Henrique Vieira; Arruda, Lucas Barbosa; Aguiar, Valbécia Tavares de; Olenchi, Maiara Magri Pereira; Serruya, Moysa Marquez; Costa, Valéria Santos da (Mastology, 2021)
Objective: To demonstrate the time between the diagnosis of the disease, the result of the immunohistochemical panel and the beginning of specialized treatment in patients diagnosed with breast cancer seen at the Foundation Center of Oncology of the State of Amazonas, from June to November 2018 and in the same period of 2019. Methods: The study was part retrospective, based on data from medical records, and part prospective, based on data from patients, and we evaluated the time between diagnosis from the immunohistochemical panel and the beginning of specialized treatment in breast cancer patients. Results: 170 patients diagnosed with breast cancer were included, 71 from June to November 2018 and 99 breast cancer patients seen from June to November 2019. The median time between diagnosis and immunohistochemistry results of all patients was 36 days, and comparing the two groups of patients, it was observed that for half of the 2018 patients, the time was less than 105 days, while for half of the 2019 patients, it was less than 27 days. If the times between the result of the immunohistochemical panel and the start of personalized treatment in both groups were compared, it was seen that the median time until the start of treatment was longer for patients in 2018, 94.5 days versus 79 days for patients in 2019. Conclusion: There was a decrease in the time between the diagnosis and the result of the molecular panel in 2019 compared to 2018. Achieving this result more quickly provided the choice of personalized treatment for each patient, having an important impact on survival in that population.